Low Superior Pubic Ramus Screw Failure Rate With Combined Anterior and Posterior Pelvic Ring Fixation. Issue 4 (April 2021) - Shieh, Alvin K.; Hayes, Christopher B.; Shelton, Trevor J.; Chip Routt, Milton L.; Eastman, Jonathan G.
Abstract : Objectives: To determine whether fracture pattern, implant size, fixation direction, or the amount of posterior pelvic ring fixation influences superior ramus medullary screw fixation failure. Design: Retrospective cohort review. Setting: Regional Level 1 trauma center. Patients/Participants: After exclusion criteria, 95 patients with 111 superior ramus fractures with 3 months minimum follow-up were included. Intervention: All patients underwent anterior and posterior pelvic ring fixation. Main Outcome Measurements: Comparison of immediate postoperative radiographs and/or computer tomography scan with the latest postoperative image to calculate interval fracture displacement and implant position. Postoperative fracture displacement or implant position change greater than 1 cm were considered fixation failures. Results: Five screws were defined as failures (4.5%), including 3 retrograde, 3 with bicortical fixation, 4 with a 4.5-mm screw, and 1 with a 7.0-mm screw. Fracture patterns included 2 oblique and 3 comminuted fractures. Based on the Nakatani classification, there were 3 zone II, 1 zone I, and 1 zone III. Failure modes included 3 with cut-out along the screw head and 1 cut-out and 1 cut-through at the screw tip. Conclusions: Our incidence of superior pubic ramus intramedullary screw fixation failure was 4.5%. Even with anterior and posterior fixation along with precise technique, failures still occur without a common failure predictor. The percutaneous advantages and proven strength provided by an intramedullary implant make it desirable to help reestablish global pelvic ring stability. Biomechanical and clinical studies are needed to further understand intramedullary superior ramus screw fixation. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.